Peningkatan Hasil Identifikasi Informasi Dalam Teks Persuasi Melalui Teknik Cerdas Cermat Pada Siswa Kelas VIII A di SMPN 2 Balong - Rufika Wahyu Yanuarista; Panji Kuncoro Hadi; Sutini (Lembaga Penelitian, Pengabdian kepada Masyarakat dan Publikasi Ilmiah (LP3M) Institut Agama Islam (IAI) Al-Qodiri Jember, Jawa Timur Indonesia bekerjasama dengan Kopertais Wilayah 4 Surabaya, 2023)
This research is based on the emergence of the phenomenon of a lack of understanding of persuasive reading in class VIII A of SMP Negeri 2 Balong. This has an impact on the ability to identify persuasive text information. In the pre-cycle implementation, the results showed that students liked learning that was shared or classical. So that this study applies a meticulous technique to improve learning outcomes in identifying persuasive text information. This research is quantitative descriptive. Data was collected using observation techniques, note-taking techniques, and giving final tests. The data used in this study is in the form of learning outcomes to identify persuasive texts obtained during 3 cycles of learning. The results show that the improvement of classical learning outcomes and the results of the final test are able to achieve minimal mastery. In classical learning cycle 1, students get an average score of 76 with a completeness percentage of 33%. In cycle 2, students get an average score of 82 with a completeness percentage of 83%. In cycle 3, students get an average score of 85 with a completeness percentage of 81%. In addition, students have better self-confidence after doing classical learning for 2 cycles. This is evident in the results of individual learning in cycle 3 which has been able to achieve a minimum percentage of completeness. Keywords: Clever; Information Identification; Persuasive Text.